The status of digital literacy and telecommunication accesses of the plantation sector in Sri Lanka - Sirikanth, S. (University of Jaffna, 2022)
Computer technologies and the Internet are dominating all aspects of political and socio-economic life in the world during the COVID-19 pandemic, which is not an exception for Sri Lanka. In this backdrop, the purpose of this study is to identify the status of digital literacy and telecommunication access in the plantation sector. This study used both qualitative and quantitative research methods and collected primary data through an online questionnaire survey. The convenience sampling method was used with 200 selected users, as well as Zoom interviews with several stakeholders in the plantation community. The secondary source of information is derived from the Department of Census and Statistics reports on computer literacy from 2006/07 to 2020 and various other secondary sources. The computer literacy rate in Sri Lanka is at a low level at 32.3 %, and the number of computer-owning households was 22.22 %, while the digital literacy rate accounts for 50.1 %. Internet usage (8.90 %) and email usage (2.54 %) are found to be very low in the estate sector. The most popular smartphone brands are Samsung (32.5 %), Huawei (15.5 %), Vivo (16 %), Oppo (10 %), and Redmi (7 %). 89.7 % of smartphones and 8.8 % of desktop/laptop devices are used to connect to the internet. The percentage of mobile subtractions used to connect to the internet is Dialog 70 %, Airtel 17 %, Mobitel 9 %, Hutch 4 %, and 28 % of them are using SLT broadband and 47 % are using Dialog broadband for the internet service at home. Inadequate technologies, low levels of education, poverty and lack of development in the plantation sector are affecting the development of the ICT sector in plantations. Effective policy and institutional measures are vitally important to address these shortcomings and move towards sustainable development of technology in the plantation sector.
Keywords: Computer literacy; Digital literacy; Plantation; Telecommunication